Soil mechanics concepts and applications - Powrie, William (CRC Press/Taylor & Francis, 2014)
This book describes the mechanical behaviour of soils as it relates to the practice of geotechnical engineering. It covers both principles and design, avoids complex mathematics whenever possible, and uses simple methods and ideas to build a framework to support and accommodate more complex problems and analysis.